High CRP and white blood cell counts are not reliable indicators of early-onset neonatal infection in full-term infants - Liu, Liang; Liu, Xueou; Zhang, Lulu; Ma, Junling; Ding, Fangrui (Frontiers in Pediatrics, 2026)
BackgroundDiagnosing neonatal early-onset sepsis (EOS) is challenging, making it difficult to determine infection indicator characteristics and cutoff values in full-term infants. This study retrospectively analyzed full-term infants with high-risk factors for neonatal EOS but tested negative for EOS, aiming to identify infection indicator characteristics and their association with perinatal factors without antibiotic intervention.MethodsFull-term infants at high risk for EOS who were admitted to rooming-in from 1 July 2023 to 29 February 2024 were included in the study. Blood routine examinations and C-reactive protein (CRP) levels were dynamically monitored after birth. All demographic data and medical records were collected from the electronic medical records system.ResultsAmong 103 neonates, only 2 had normal infection indicators. Within 24–48 h after birth, an additional 28 displayed normal infection indicators. Although most of the infants exhibited normal WBC within 24–48 h, 33 patients still had higher neutrophil percentages, and 62 had higher CRP levels. Moreover, several high-risk perinatal factors for abnormal infection indicators have been identified.ConclusionsThis study demonstrates that infection indicators frequently showed abnormalities in full-term infants at high risk for EOS who tested negative. Few infants had normal infection indicators within 24 h, and although WBC levels normalized by 24–48 h, CRP levels remained elevated. Specific perinatal factors were also associated with abnormal infection markers. These findings reinforce the need for cautious interpretation of isolated biomarker elevations and support antimicrobial stewardship by highlighting the high frequency of abnormal indicators in uninfected infants, thereby reducing unnecessary antibiotic exposure.